Comparison of Intraocular Pressure, Usage of Topical Steroids, Need for Intraocular Pressure Lowering Drops, and Incidence of Glaucoma Surgery Up to 2 Years After Penetrating Keratoplasty and Endothelial Keratoplasty. Issue 12 (December 2020) - Vu, Priscilla Q.; Aggarwal, Sahil; Lu, Yvonne; Xie, Kate; Wade, Matthew; Bhatt, Anand
Abstract : Precis: A retrospective review of 239 eyes comparing intraocular pressure (IOP), steroid needs, IOP-lowering drop needs, and incidence of glaucoma surgery between endothelial keratoplasty and penetrating keratoplasties (PKP) at multiple timepoints postoperatively up to 2 years. Purpose: The purpose of this study was to compare postoperative IOP, steroid use, IOP-lowering drop use, and need for glaucoma surgery between PKP, Descemet membrane endothelial keratoplasty (DMEK) and Descemet stripping automated endothelial keratoplasty (DSEK). Materials and Methods: A retrospective chart review of all PKP, DMEK, and DSEK surgeries was performed between July 1, 2012 and July 1, 2017 at the University of California, Irvine. Patients with a prior history of glaucoma, corneal or glaucoma surgery, concurrent major or emergent surgery, active infection, and eye disease with synechiae were excluded. A total of 239 patients who underwent PKP (N=127), DMEK (N=46), or DSEK (N=66) were included. IOP, steroid use, IOP-lowering drop use, and need for glaucoma surgery were compared at postoperative day 1, postoperative week 1 (POW1), and postoperative month 1 to 24 (POM1-24). Results: IOP for PKP was higher than DMEK and DSEK at POW1, POM1, POM6, and POM24 ( P <0.05). IOP for PKP was higher than DMEK at POM12 ( P =0.028). There was no significant difference in IOP between DMEK and DSEK for all timepoints. PKP required more steroids than DSEK and DMEK at POM3, POM6, POM12, and POM24 ( P <0.05). More IOP-lowering drops were required for DSEK than DMEK and PKP at postoperative day 1 and POW1 ( P <0.05). More IOP-lowering medications were used for DSEK than DMEK at POM3 and POM12 ( P <0.05). About 6% to 7% of patients needed glaucoma surgery by POM24. Conclusions: Endothelial keratoplasties had decreased IOP and steroid needs compared with PKPs postoperatively up to 2 years. The rate of glaucoma surgery and IOP-lowering drop needs were similar between the groups.